The Effect of Health Education Using Audiovisuals on The Knowledge of Adolescent Girls about Breast Self-Examination (BSE) - Aesza Okty Zull Fanny; Bunga Tiara Carolin; Putri Azzahroh (KHD Production, 2024)
Cancer is a non-communicable disease with the second-largest death rate in the world. Breast cancer is one of the main diseases treated by palliative care services. Breast cancer is the most common cancer among women in the world. Early detection is a very important first step to find out early the presence of tumors or lumps in the breast to reduce the death rate due to cancer. The advantage of early detection of breast cancer is beneficial to increase the chances of life expectancy in women with breast cancer. Almost 85% of disorders or lumps are found by the patient through proper examination. In addition, BSE is the easiest, fastest, cheapest, and simplest method that can detect breast cancer early. Knowing the Effect of Health Education Using Audio Visual Media on Adolescent Girls' Knowledge about BSE at SMAN 10 Tangerang Regency Banten 2023. The research design used was quasi-experimental research with a one-group pretest-posttest design approach. The population used in this study was class X adolescent girls at SMAN 10 Tangerang Regency totaling 155 people. The number of samples taken was 30 samples obtained through the Proportionate Stratified Random Sampling technique. Data were collected using a questionnaire. Data analysis was done by Paired T Test. The results of univariate analysis before conducting health education using audio-visual video exposure were 10.67, while the average knowledge of adolescent girls increased after health education to 15.60. The results of bivariate analysis with paired sample t-test P value = 0.001 means that there is an effect of counseling with audiovisual media on increasing the knowledge of adolescent girls about breast self-examination. Using audiovisual media to increase knowledge about breast self-examination (BSE) for early detection of cervical cancer.